Effect of Cranberry in Enhancing Oral Hypoglycemic Agents in Uncontrolled Type-II Diabetic Patients - Atheer Majid Rashid Al-Juhaishi (Journal of Global Pharma Technology, 2018)
Diabetes mellitus (DM) is one of the most common metabolic disorders associated with morbidity and mortality. Type II diabetes may be due to peripheral insulin resistance, defected insulin secretion or both. Cranberries are an evergreen class of midget sapling in the subgenus Oxycoccus of genus Vaccinium and have many pharmacological effects including antibacterial, antioxidant, cardio protective activity, anticancer, and hypoglycemic effects. The aim of this study is to assess the effect of cranberry in enhancingoral hypoglycemic agents in uncontrolled type II diabetic patients. The population sample consists of 60 type II diabetic patients aged between 35 and 63 years who met the diagnostic criteria of type II DM. Each patient was assessed individually using a case sheet that including age & sex, medical history and medication history. They were divided into two groups; the 1st group was treated with metformin and sulfonylurea alone, the 2nd group were treated with those agents plus cranberry capsules as add on treatment. The results showed significantly decline in blood glucose & glycated hemoglobin (HbA1c) which was changed from uncontrolled level 9.51% to controlled level 6.97% with aid of cranberryin group 2 in comparison with its change from 9.38% to 7.65% with oral hypoglycemic agents alone in group1 (p-value <0.0001). In conclusion, cranberry has a good hypoglycemic effect in treatment of type II DM and enhancing the effect of oral hypoglycemic agents.Keywords: Cranberry, Type II diabetes, FBS, HbA1c.